Análise da formação de camada limite interna em regiões costeiras tropicais utilizando sondagens acústicas e o modelo atmosférico WRF - Aragão, Leonardo Ferreira da Silva (2018)
This thesis investigates local circulation features in the industrialized coastal region of Santa Cruz, Rio de Janeiro. The topographic characteristics and the variety of atmospheric phenomena acting over the area suggest the formation of Internal Boundary Layers (IBLs) during cold front and bay breeze flows with direction upstream of the major industries. Vertical profiles of main meteorological variables are evaluated together with surface weather stations, satellite data, and atmospheric modelling using WRF to derive a detailed physics-based description of the various stages of bay breeze in terms of the main forces, duration, and atmospheric stabilities. It is found that the development phase of the sea breeze coincides with the largest bay land differences and, consequently, it is the most pronounced condition to observe the IBL formation. Furthermore, a suitable refinement at WRF vertical levels proved to be fundamental to become possible the phenomena representation, as well as a good estimate for IBL main characteristics (height and fetch).